2000
DOI: 10.1002/(sici)1099-114x(200004)24:5<455::aid-er602>3.0.co;2-5
|View full text |Cite
|
Sign up to set email alerts
|

Tertiary fatty amides as diesel fuel substitutes

Abstract: This paper presents experimental results regarding the impact of adding different tertiary amides of fatty acids to mineral diesel fuel; an assessment of the behaviour of these compounds as possible diesel fuel extenders is also included. Measurements of cetane number, cold flow properties (cloud point, pour point and CFPP), density, kinematic viscosity, flash point and distillation temperatures are reported, while initial experiments concerning the effects on particulate emissions are also described. Most of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 4 publications
0
10
0
Order By: Relevance
“…methanol or ethanol [5]. In the past few decades, biodiesel has received increased attention as it offers many environmental benefits such as renewable, non-toxic, biodegradable, contains zero sulfur and aromatic substances [1][2][3][4][5]. Furthermore, it can be mixed with petroleum-diesel in any proportion and directly used in engines with no need additional modifications [1].…”
Section: Introductionmentioning
confidence: 99%
“…methanol or ethanol [5]. In the past few decades, biodiesel has received increased attention as it offers many environmental benefits such as renewable, non-toxic, biodegradable, contains zero sulfur and aromatic substances [1][2][3][4][5]. Furthermore, it can be mixed with petroleum-diesel in any proportion and directly used in engines with no need additional modifications [1].…”
Section: Introductionmentioning
confidence: 99%
“…Three previous studies in our laboratory showed that the esters of mono-and di-carboxylic acids, acetoacetates, aliphatic amines and tertiary amides are five interesting categories of diesel fuel extenders as they incorporate very good cetane rating with satisfactory cold flow performance, and they fulfill the rest of the diesel fuel specifications [27][28][29]. Another important result from our experiments was the beneficial impact of these oxygen and nitrogen compounds tested on particulate matter emissions from internal combustion engines, where in all cases, a reduction in particulate matter emissions was observed, especially in higher loads.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, fatty acid amide derivatives (FADs) termed to be more useful than ester derivates in biodiesel technology as they have better ignition properties. 16,17 Also, fatty acid amides derived from natural triglycerides are completely free from sulfur or aromatic compounds and hence help to reduce the greenhouse effect, improve cetane number, cold flow characteristics, and a positive effect on particulate matter emissions. 16 Sodium hydroxide, potassium hydroxide, sodium methoxide, and potassium methoxide are the most commonly used homogeneous basic catalysts used for FAMEs synthesis although they are very sensitive towards moisture content and high free fatty acid (FFA) contents.…”
Section: Introductionmentioning
confidence: 99%
“…16,17 Also, fatty acid amides derived from natural triglycerides are completely free from sulfur or aromatic compounds and hence help to reduce the greenhouse effect, improve cetane number, cold flow characteristics, and a positive effect on particulate matter emissions. 16 Sodium hydroxide, potassium hydroxide, sodium methoxide, and potassium methoxide are the most commonly used homogeneous basic catalysts used for FAMEs synthesis although they are very sensitive towards moisture content and high free fatty acid (FFA) contents. [18][19][20] Also, removing homogeneous catalysts (acid or base) from products needs a lot of washing with water, which in turn leads to water wastage and increased process cost.…”
Section: Introductionmentioning
confidence: 99%